Effects of Wall and Individual Underhand Passing Practice on Volleyball Accuracy for Middle School Students - Hasmuddin Hasmuddin; Hikmad Hakim; Sahabuddin Sahabuddin; Muh. Adnan Hudain (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Underhand passing is a crucial foundation in volleyball, yet many students still struggle to achieve consistent accuracy. This study aims to analyze the effectiveness of wall-passing training compared to individual passing training in improving underhand passing accuracy at middle school 1 Pamboang. This research utilized a quasi-experimental design with a Two-Group Pretest–Posttest approach involving 20 students as the target population. Data was collected through passing accuracy tests before and after the treatment, which were then systematically tabulated and analyzed using descriptive and inferential statistical techniques. The results demonstrated that both training models made a significant positive contribution to improving students' abilities. The wall-passing training group recorded a substantial increase in average scores, rising from 10.50 during the pre-test to 18.90 in the post-test. Meanwhile, the individual passing training group also experienced an improvement, with mean scores increasing from 10.40 to 16.60. Although both methods were proven effective, descriptive data indicated that the wall-passing group achieved a higher final performance level than the individual passing group. These findings suggest that wall media is highly effective for building basic technical consistency and accuracy before students progress to more complex situational drills.